Dominant Capital and the Government - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2021)
This note contextualizes the ongoing U.S. policy shift toward greater `regulation' of large corporations. Cory Doctorow and Blair Fix are optimistic about this shift. We doubt it.
Keywords: P16; P26; P48; I18; K2; L; 330; capital as power; dominant capital; government; mode of power; policy; regulation; United States